Liposomal Targeting of Prednisolone Phosphate to Synovial Lining Macrophages during Experimental Arthritis Inhibits M1 Activation but Does Not Favor M2 Differentiation - Hofkens, Wouter; Schelbergen, Rik; Storm, Gert; van den Berg, Wim B.; van Lent, Peter L. (PLOS ONE, 2013)
Background To determine the effects of liposomal targeting of prednisolone phosphate (Lip-PLP) to synovial lining macrophages on M1 and M2 polarization in vitro and during experimental arthritis. Material and Methods Experimental arthritis (antigen and immune complex induced) was elicited in mice and prednisolone containing liposomes were given systemically. Synovium was investigated using microarray analysis, RT-PCR and histology. Bone–marrow macrophages were stimulated towards M1 using LPS and IFNγ before treatment by PLP-liposomes. M1 and M2 markers were determined using RT-PCR. Results Microarray analysis of biopsies of inflamed synovium during antigen induced arthritis (AIA) showed an increased M1 signature characterized by upregulation of IL-1β, IL-6 and FcγRI starting from day 1 and lasting up until day 7 after arthritis induction. The M2 signature remained low throughout the 7 day course of arthritis. Treatment of AIA with intravenously delivered Lip-PLP strongly suppressed joint swelling and synovial infiltration whereas colloidal gold containing liposomes exclusively targeted the macrophages within the inflamed synovial intima layer. In vitro studies showed that Lip-PLP phagocytosed by M1 macrophages resulted in a suppression of the M1 phenotype and induction of M2 markers (IL-10, TGF-β, IL-1RII, CD163, CD206 and Ym1). In vivo, Lip-PLP treatment strongly suppressed M1 markers (TNF-α, IL-1β, IL-6, IL-12p40, iNOS, FcγRI, Ciita and CD86) after local M1 activation of lining macrophages with LPS and IFN-γ and during experimental AIA and immune complex arthritis (ICA). In contrast, M2 markers were not significantly upregulated in antigen-induced arthritis and down regulated in immune complex arthritis. Conclusion This study clearly shows that systemic treatment with PLP-liposomes selectively targets synovial lining macrophages and inhibits M1 activation. In contrast to in vitro findings, PLP-liposomes do not cause a shift of synovial lining macrophages towards M2.